Terminação de cordeiros e borregos da raça Corriedale submetidos à dietas de alto concentrado - Venturini, Rafael Sanches (2015)
The experiment was conducted with the objective of evaluating the nutrients intake, weight gain, economic viability (chapter I), ingestive behavior (chapter II) and carcass and non carcass components characteristics (chapter III) of Corriedale lambs and hoggets submitted to high concentrate diets based on corn or sorghum grain. Thirty- two Corriedale ovines, being 16 lambs (milk teeth) and 16 hoggets (two teeth), male and castrated were used. The animals were divided into: 8 lambs fed with corn high concentrate diet; 8 lambs fed with sorghum high concentrate diet; 8 hoggets fed with corn high concentrate diet and 8 hoggets fed with sorghum high concentrate diet. The diets were constituted by white oat hay (Avena sativa), corn (Zea mays) or sorghum grain (Sorghum bicolor (L.) Moench), supplied as whole grain, soybean meal (Glycine Max), limestone, sodium bicarbonate and monensin. No interaction between animal category and type of tested grain was observed for any of the analyzed variables. The lambs presented greater (P≤0.05) dry matter (DMI) (%LW and g/kg LW0,75), crude protein (CPI) (kg/day, % do LW and g/kg LW0,75), ether extract (EEI) (% of LW), neutral detergent fiber (NDFI), acid detergent fiber (ADFI) (% of LW and g/kg LW0,75), total digestible nutrients (TDNI) (% of LW) intake, daily average gain (DAG), conformation (CONF) and feed conversion (FC), and also presented better economic results when compared to the hoggets. Moreover, the lambs presented a longer total chewing time (min/day and %), other activities (min/day and %), number of meals per day, fasting losses (FL) and percentage of external and internal organs. On the other hand, the ether extract (EEI), total carbohydrates (TCI) and non structural carbohydrates (NSCI) intake, expressed in kg/day, the initial live weight (ILW), final live weight (FLW), live weight at slaughter (LWS), idle time (min/day and %), time spent per meal, the DM or NDF weight ingested per meal, hot carcass weight (HCW), cold carcass weight (CCW), hot carcass yield (HCY), cold carcass yield (CCY), carcass compactness index (CCI), subjective color (SC), rib eye area (REA) and neck (NEC), palette (PAL), sidecut (SCUT) and leg (LEG) weight were superior (P≤0,05) in the hoggets category. It was verified a higher (P≤0.05) EEI (kg/day, % do LW and g/kg LW0,75), longer feeding and total chewing time (min/day and %) and greater SCUT (%), as well as lower (P≤0,05) NDFI (% of LW) and ADFI (kg/day, % do LW and g/kg LW0,75), for the animals fed with high concentrate diet based in corn grain. The idle time (min/day and %), feeding efficiency (g DM/h and g NDF/h), HCY, CCY and SC were greater in the lambs fed with diets based on sorghum grain. The productive indices presnted by lambs were better than thoses presented by hoggets. For corn and sorghum grain test The results showed influence of the bromatological composition of the grains.